Penerapan Disiplin Kerja Karyawan di PT Gojek - Joshua Valerio; Oktavian Tri Pandowo; Yuga Arya Kencana; Mohamad Zein Saleh (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study explores the implementation of employee work discipline at PT Gojek and its impact on company productivity. Using the literature study method, this study highlights how work discipline manifested in compliance, responsibility, and giving to work regulations contributes to effectiveness. The results of the study indicate that work discipline has a significant influence on performance and service quality. The conclusion of the study states that the implementation of clear rules, effective communication, and consistent supervision are very important in building a disciplined and competitive work environment, especially in technology-based service companies.